IMPROVING THE PERFORMANCE OF UNSIGNALIZED T-INTERSECTIONS WITHIN CAVS MIXED TRAFFIC - Alanazi, Fyaez; Yi, Ping; EL Gehawi, Nader (Journal of Applied Engineering Science, 2022)
The rapid growth in population and the increase in the number of vehicles on the road have resulted in severe traffic congestion over the last two decades. However, intersections, where different flows intersect, are among the major cause of traffic congestion besides bottlenecks. Past decades have seen major technological advancements in road vehicles aimed at making vehicles traveling securely and comfortably. Current connected and automated vehicles (CAV) are packed with lane-keeping assistance and adaptive cruise control to ensure that vehicles do not collide and reduce traffic congestion. In this research, we developed a control algorithm that utilizes CAVs to help generate additional usable gaps for the minor road vehicles to enter the intersection without affecting the mainline traffic flow. Simulation results showed that the delay and queue length of the minor road approach is minimized without causing a significant delay to the mainline. The minor road delay was reduced by 72% when the percentage of CAVs on the major road is 70% compared to the benchmark with no CAVs on the major road.
Keywords: CAVs, connected and automated vehicles, unsignalized intersections, gap acceptance, intersection priority, merging capacity